Infinitely Many Solutions for a Steklov Problem Involving the p(x)-Laplacian Operator - Armin Hadjian (پژوهش‌های ریاضی, 2018)
By using variational methods and critical point theory for smooth functionals defined on a reflexive Banach space, we establish the existence of infinitely many weak solutions for a Steklov problem involving the p(x)-Laplacian depending on two parameters. We also give some corollaries and applicable examples to illustrate the obtained result../files/site1/files/42/4Abstract.pdf